Photocatalytic oxidative dearomatization of orcinaldehyde derivatives - Dockrey, Summer A. Baker (Org Lett, 2020)
For decades oxidative dearomatization has been employed as a key step in the synthesis of complex molecules. Challenges in controlling the chemo- and site-selectivity of this transformation have sparked the development of a variety of specialized oxidants; however, these result in stoichiometric amounts of organic byproducts. Herein, we describe a photocatalytic method for oxidative dearomatization using molecular oxygen as the stoichiometric oxidant. This provides environmentally benign entry to highly substituted o-quinols, reactive intermediates which can be elaborated to a number of natural product families.